Teaching Showing Ability Through Songs: How Effective Is It for Students Listening Comprehension? - Trisnawati, Komang Ayu; Utami, I Gusti Ayu Lokita Purnamika; Suprianti, G.A.P. (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
The aim of this research was to investigate students’ listening comprehension through the use of song as a media under the topic of showing ability for EFL student. This research was a quasi-experiment involving 80 students (40 in control and experiment group). Test of listening comprehension was used to collect the data. The samples were chosen using multistage cluster sampling. Findings showed that there is a significant difference in post-test scores between the two groups, namely the group that favors the experimental group. The independent t-test proved that the value of sig two-tailed its 0.000 was lower than 0.05 which interpreted that Songs has a significant impact on students' listening comprehension. In addition, students t students had positive attitudes and responses towards the use of songs in listening classes. Students felt that the songs given as material succeeded in making students enthusiastic and moving their bodies. It was an interesting activity including listening practice which was meaningful for them so that they felt more motivated and happier in learning English. Suggestions for teachers and further research are encouraged in this article.